Analisis Tentang Konsep Pengosongan Sukarela dalam Penyelesaian Sengketa Properti - Yoga, Agung Brahmanda; Siki, Renhat M.; Yadnya, Putu Andhika Kusuma (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
This research focuses on the concept of voluntary vacating in property dispute resolution, emphasizing its importance in achieving fair and effective outcomes. It delves into the legal framework surrounding voluntary vacating and its implications for justice, legal certainty, and human rights protection. Through a normative legal research approach, supported by literature review and descriptive analysis, the study explores the process and significance of voluntary vacating in resolving property disputes. The findings underscore the need for careful consideration of human rights principles and procedural fairness throughout the voluntary vacating process to ensure equitable outcomes for all parties involved.